Reliable Multipath Communication Approach for Internet-based Cyber-physical Systems - Elattar, Mohammad; Jasperneite, Jürgen; Trächtler, Ansgar; et, al (26th IEEE International Symposium on Industrial Electronics (ISIE))

Flachheitsbasierte Positionsregelungen für Parallelkinematiken am Beispiel eines hochdynamischen Hexapoden - Knoop, Sarah

Mechanisch - mathematisches Modell eines Kettenfahrzeuges für die Entwicklung innovativer Antriebs- und Federungssysteme (auf russ.) - Poddubny, Wladimir; Trächtler, Ansgar; Warkentin, Andreas P.; Krüger, Martin (Interbranch Scientific and Technical Magazine «Vestnik Mashinostroeniya»)

Integrierte, selbstoptimierende Fahrdynamikregelung mit Einzelradaktorik - Reinold, Peter

Indirect Force Control in Hardware-in-the-Loop Simulations for a Vehicle Axle Test Rig - Olma, Simon; Kohlstedt, Andreas; Traphöner, Phillip; Jäker, Karl-Peter; Trächtler, Ansgar (14th International Conference on Control, Automation Robotics & Vision (ICARCV))

Feature Model Based Interface Design for Development of Mechatronic Systems

PROFINET-Implementierung im Rahmen der Entwicklung eines intelligenten, selbstlernenden Teigkneters - Holtkötter, Jens; Michael, Jan; Henke, Christian; Trächtler, Ansgar; Oestersötebier, Felix; Wessels, Sebastian (Virtuelle Instrumente in der Praxis 2016)

A HRRN based scheduling for FMS and RMS with networked control and product-intelligence - Bertelsmeier, Fabian; Pollmann, Jan; Trächtler, Ansgar (Inproceedings of the IEEE IECON 2016)

Model Predictive Feedforward Compensation for Control of Multi Axes Hybrid Kinematics on PLC - Rüting, Arne Thorsten; Blumenthal, Lars Martin; Trächtler, Ansgar (Proceedings of IEEE IECON 2016)

Nichtlineare Zustandsregelung mit Sliding-Mode-Beobachter für einen Achsprüfstand mit hydraulischem Hexapoden - Olma, Simon; Traphöner, Phillip; Kohlstedt, Andreas; Trächtler, Ansgar (GMA Fachausschuss 1.40 "Theoretische Verfahren der Regelungstechnik")

Substructuring and Control Strategies for Hardware-in-the-Loop Simulations of Multiaxial Suspension Test Rigs - Olma, Simon; Kohlstedt, Andreas; Traphöner, Phillip; Jäker, Karl-Peter; Trächtler, Ansgar (Proceedings of the 7th IFAC Symposium on Mechatronic Systems)

Study of a rail-bound parallel robot concept with curvilinear closed-path tracks - Bielawny, Dirk; Wang, Peng; Trächtler, Ansgar (Proceedings of 7th IFAC Symposium on Mechatronic Systems & 15th Mechatronics Forum International Conference)

Multiobjective Model Predictive Control of an Industrial Laundry - Peitz, Sebastian; Graeler, Manuel; Henke, Christian; Hessel-von Molo, Mirko; Dellnitz, Michael; Trächtler, Ansgar (3rd International Conference on System-integrated Intelligence: New Challenges for Product and Production Engineering)

Design and Implementation of Intelligent Control Software for a Dough Kneader - Oestersötebier, Felix; Traphöner, Phillip; Reinhart, Felix; Wessels, Sebastian; Trächtler, Ansgar (Proceedings of the 3rd International Conference on System-Integrated Intelligence)

Approach for an Integrated Model-Based System Design of Intelligent Dynamic Systems Using Solution and System Knowledge - Oestersötebier, Felix; Abrishamchian, Farisoroosh; Lankeit, Christopher; Just, Viktor; Trächtler, Ansgar (Proceedings of the 3rd International Conference on System-Integrated Intelligence)

Model-based method for the accuracy analysis of Hardware-in-the-Loop test rigs for mechatronic vehicle axles - Olma, Simon; Traphöner, Phillip; Kohlstedt, Andreas; Jäker, Karl-Peter; Trächtler, Ansgar (Proceedings of the 3rd International Conference on System-Integrated Intelligence)

Disturbance Observer Design for Utilizing of Time-delayed Vision Measurements in High Dynamic Systems - Wang, Shuo; Just, Viktor; Trächtler, Ansgar (Proceedings of the 3rd International Conference on System-Integrated Intelligence)

Development and design of intelligent product carriers for ﬂexible networked control of distributed manufacturing processes - Bertelsmeier, Fabian; Schöne, Stefan; Trächtler, Ansgar (Inproceedings of the IEEE 24th Mediterranean Confernce on Control and Automation (MED))

Control of a hydraulic hexapod for a Hardware-in-the-Loop axle test rig - Kohlstedt, Andreas; Olma, Simon; Flottmeier, Sarah; Traphöner, Phillip; Jäker, Karl-Peter; Trächtler, Ansgar (at-Automatisierungstechnik)

Consistency Analysis for Requirements, Functions, and System Elements - Lankeit, Christopher; Just, Viktor; Trächtler, Ansgar (IEEE Systems Conference)

Modellbildung und Simulation im Kontext des Systems Engineering - Michael, Jan; Holtkötter, Jens; Henke, Christian; Trächtler, Ansgar (ASIM-Treffen STS/GMMS 2016)

Implementing intelligent technical systems into smart homes by using model based systems engineering and multi-agent systems - Michael, Jan; Hillebrand, Michael; Wohlers, Benedict; Henke, Christian; Dumitrescu, Roman; Trächtler, Ansgar (Renewable Energy and Power Quality Journal (RE&PQJ) 16)

Precision Control of SMA Actuators with a Real Time Model-Based Controller and Extended VSC - Pai, Arathi; Riepold, Markus; Trächtler, Ansgar (IFAC-PapersOnLine)

Regelungstechnik - Föllinger, Otto; Konigorski, Ulrich; Lohmann, Boris; Roppenecker, Günter; Trächtler, Ansgar

A model extended temperature and strain controller modulated with PWM for precision position control of shape memory alloy actuators - Pai, Arathi; Riepold, Markus; Trächtler, Ansgar (IEEE International Conference on Advanced Intelligent Mechatronics AIM)

Multidomänenmodell zur Optimierung der Hydraulik eines Raupenlaufwerks für Landmaschinen - Kruse, Daniel; Warkentin, Andreas P.; Krüger, Martin; Trächtler, Ansgar; Rackow, Sascha (Proc. 4. Internationales Commercial Vehicle Technology Symposium)

Consensus-based local information coordination for the networked control of the autonomous intersection management - Wuthishuwong, Chairit; Trächtler, Ansgar (Complex & Intelligent Systems)

Simultaneous path planning and trajectory optimization for robotic manipulators using discrete mechanics and optimal control - Shareef, Zeeshan; Trächtler, Ansgar (Robotica)

Verbesserte Schätzung von Fahrdynamikgrößen durch Modellierung der Fahrwerks-und Lenkkinematik - Renninger, Johannes; Trächtler, Ansgar (at-Automatisierungstechnik)

A Novel Approach Using Model Predictive Control to Enhance the Range of Electric Vehicles - Eckstein, Julian; Lüke, Christopher; Brunstein, Frederik; Friedel, Patrick; Köhler, Ulrich; Trächtler, Ansgar (3rd International Conference on System-integrated Intelligence: New Challenges for Product and Production Engineering, SysInt 2016)

Feature Model Approach For Managing Variability of Dynamic Behavior Models in Mechatronic Systems - Abrishamchian, Farisoroosh; Oestersötebier, Felix; Trächtler, Ansgar (Proceedings of the ASME 2015 International Mechanical Engineering Congress & Exposition)

Decentralized Controller Reconﬁguration Strategies for Hybrid System Dynamics based on Product-Intelligence - Bertelsmeier, Fabian; Trächtler, Ansgar (20th IEEE International Conference on Emerging Technologies and Factory Automation)

Flexible Operation Workflow of a Driving Simulation Center for ADAS Development - Abdelgawad, Kareem; Hassan, Bassem; Kohlstedt, Andreas; Stöcklein, Jörg; Berssenbrügge, Jan; Grafe, Michael; Gausemeier, Sandra; Jäker, Karl-Peter; Trächtler, Ansgar (New Developments in Driving Simulation Design and Experiments)

ARTiST - An Augmented Reality Testbed for Intelligent Technical Systems - Hassan, Bassem; Stöcklein, Jörg; Berssenbrügge, Jan (Virtual, Augmented and Mixed Reality VAMR 2015 Held as Part of HCI International 2015)

Visualization of Headlight Illumination for the Virtual Prototyping of Light-Based Driver Assistance Systems - Berssenbrügge, Jan; Trächtler, Ansgar; Schmidt, Christoph (Proceedings of the ASME 2015 International Design Engineering Technical Conferences & Computers and Information in Engineering Conference)

Parametrische Modellordnungsreduktion für hierarchische selbstoptimierende Systeme - Krüger, Martin; Trächtler, Ansgar (at-Automatisierungstechnik)

Produkt- und lastabhängiges dezentrales Motormanagement für die Fördertechnik: Anforderungen, Design und Applikation - Bertelsmeier, Fabian; Vathauer, Marc; Henke, Christian; Vathauer, Karl-Ernst; Trächtler, Ansgar (Automation 2015)

Modelling the Constitutive Behaviour of Martensite and Austenite in Shape Memory Alloys Using Closed-Form Analytical Continuous Equations - Pai, Arathi; Niendorf, Thomas; Krooß, Philipp; Koke, Isabel; Trächtler, Ansgar; Schaper, Mirko (7th ECCOMAS Thematic Conference on Smart Structures and Materials - SMART)

Intelligente Biegeverfahren - Damerow, Ulf-Hendrik; Borsig, Michael; Tabakajew, Dmitri; Schaermann, Waldemar; Hesse, Marc; Homberg, Werner; Trächtler, Ansgar; Jungeblut, Thorsten (wt Werkstattstechnik online)

A Modular Architecture of an Interactive Simulation and Training Environment for Advanced Driver Assistance Systems - Abdelgawad, Kareem; Hassan, Bassem; Berssenbrügge, Jan; Stöcklein, Jörg; Grafe, Michael (International Journal On Advances in Software)

Design and Control of Cooperative Ball Juggling Delta Robots without Visual Guidance - Shareef, Zeeshan; Just, Viktor; Teichrieb, Heinrich; Trächtler, Ansgar (Robotica)

Path Planning and Trajectory Optimization of Delta Parallel Robot - Shareef, Zeeshan

Automatische Ableitung geometrischer Eigenschaften von Bauteilen aus dem 3-D-Polygonmodell - Jähn, Claudius; Fischer, Matthias; Gerges, Maria; Berssenbrügge, Jan (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Visualisierung von Scheinwerfersystemen für das Virtual Prototyping von lichtbasierten Fahrerassistenzsystemen - Berssenbrügge, Jan; Trächtler, Ansgar; Schmidt, Christoph; Stöcklein, Jörg; Grafe, Michael (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Anbindung des Virtuellen Prototypen an die Partialmodelle intelligenter technischer Systeme - Berssenbrügge, Jan; Wiederkehr, Olga; Jähn, Claudius; Fischer, Matthias (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Entwicklung eines prädiktiven Motion-Cueing-Verfahrens für den ATMOS-Fahrsimulator - Zimmermann, Daniel; Kohlstedt, Andreas; Gausemeier, Sandra; Trächtler, Ansgar (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Online-Rekonﬁguration hybrider Regelkreise in Abhängigkeit variierender Produkteigenschaften - Bertelsmeier, Fabian; Engelmeier, Tobias; Trächtler, Ansgar (Tagungsband Mechatronik 2015)

Systematische Wahl der Modellierungstiefe im Entwurfsprozess mechatronischer Systeme am Beispiel eines Geldautomaten - Lochbichler, Matthias; Lankeit, Christopher; Trächtler, Ansgar; Landwehr, Martin; Hoischen, Ludger (Tagungsband Mechatronik)

Tutorenprogramm und Vertiefungsberatung stellen Weichen in entscheidenden Phasen des Student Life-Cycles in Maschinenbaustudiengängen - Koke, Isabel; Dibblee, Katharina; Hankeln, Frederik; Seidel, Stefan; Trächtler, Ansgar; Schmid, Hans-Joachim (44. Jahrestagung der Deutschen Gesellschaft für Hochschuldidaktik - Hochschuldidaktik im Dialog, Paderborn)

Modellbasierte Mehrzieloptimierung zur Integration von Hausgeräten in SmartGrids - Michael, Jan; Hillebrand, Michael; Dumitrescu, Roman; Henke, Christian; Trächtler, Ansgar (VDI Mechatronik 2015 Tagungsband)

Safe trajectory planning for autonomous intersection management by using vehicle to infrastructure communication - Wuthishuwong, Chairit; Trächtler, Ansgar; Bruns, Torsten (EURASIP Journal on Wireless Communications and Networking)

Challenges in Requirements Engineering for Mechatronic Systems – Problem Analysis and First Approach - Lankeit, Christopher; Lochbichler, Matthias; Trächtler, Ansgar (Jurnal Teknologi)

From Goals to Systems via Technical Requirements and Physical Models - Design of an Intelligent Cash Handling System - Lankeit, Christopher; Lochbichler, Matthias; Oestersötebier, Felix; Trächtler, Ansgar; Landwehr, Martin (Proceedings)

Real-Time Compatible Phenomenological Modelling of the Austenitic Phase in Shape Memory Alloys as an Example for Modelling of Materials with Repeatable Non-Linear Characteristics - Pai, Arathi; Trächtler, Ansgar; Schaper, Mirko (IFAC 1st Conference on Modelling, Identification and Control of Nonlinear Systems - MICNON)

Flachheitsbasierte Methode zum stoßfreien Umschalten von Reglerstrukturen - Osmic, Semir

Influences of process parameters on the mechanical properties of hybrid sheet metal-FRP-composites manufactured by prepreg press technology - Lauter, Christian; Wang, Zheng; Koke, Isabel; Tröster, Thomas (20th International Conference on Composite Materials, Copenhagen)

Virtual Commissioning by Means of an Adaptive Selection of the Modeling Depth - Frieben, Tanja; Trächtler, Ansgar (Proceedings of the ASME 2014 International Mechanical Engineering Congress & Exposition IMECE14, Montreal, Québec, Canada)

Methodology for a Partly Automated Parameter Identification for the Validation of Multi-Domain Models - Kruse, Daniel; Schweers, Christoph; Trächtler, Ansgar (Proceedings of the ASME 2014 International Mechanical Engineering Congress & Exposition IMECE 2014)

Dynamic Behavior Models and their Modeling Depth in the Design Process of Mechatronic Systems - Lochbichler, Matthias; Oestersötebier, Felix; Trächtler, Ansgar (Proceedings of the ASME 2014 International Mechanical Engineering Congress & Exposition IMECE 2014)

Ansätze zur Regelung eines elektronischen Lastemulators für die Hardware-in-the-Loop-Simulation von Antriebsreglern auf Leistungsebene - Kromov, Ivan; Deter, Matthias; Trächtler, Ansgar (SPS IPC Drives)

Optimal Trajectory Planning for Robotic Manipulators Using Discrete Mechanics and Optimal Control - Shareef, Zeeshan; Trächtler, Ansgar (Multi-Conference on Systems and Control (MSC) / 23rd Conference on Control Applications (CCA))

Analysis of high speed bending operations as basis for integrating self-correcting components to increase process reliability - Damerow, Ulf-Hendrik; Borsig, Michael; Tabakajew, Dmitri; Schaermann, Waldemar; Homberg, Werner; Trächtler, Ansgar (Procedia Engineering 81)

Parametrische Modellordnungsreduktion für hierarchische selbstoptimierende Systeme - Krüger, Martin (Workshop GMA-Fachausschuss 1.30)

Subjective Evaluation of Different Motion Cueing Algorithms Implemented on ATMOS Driving Simulator - Al Qaisi, Imad; Zimmermann, Daniel; Kohlstedt, Andreas; Gausemeier, Sandra; Trächtler, Ansgar (Driving Simulation Conference 2014)

Consensus coordination for multiple autonomous intersection management - Wuthishuwong, Chairit; Trächtler, Ansgar (Tagungsband 9. Dortmunder AutoTag)

Modellbasierte Analyse und regelungstechnische Maßnahmen zur Optimierung des Vereinzelungsvorgangs in Bankautomaten - Just, Viktor

Stability of the consensus in the network of multiple Autonomous Intersections Management - Wuthishuwong, Chairit; Trächtler, Ansgar (Proc. 20th International Conference on Automation and Computing (ICAC))

Simultaneous Path Planning and Trajectory Optimization for Robotic Manipulators using Discrete Mechanics and Optimal Control - Shareef, Zeeshan; Trächtler, Ansgar (Robotica)

Consensus Coordination in the Network of Autonomous Intersection Management - Wuthishuwong, Chairit; Trächtler, Ansgar (Proc. 11th International Conference on Informatics in Control Automation and Robotics ICINCO)

Sliding Mode and Continuous Estimation Techniques for the Realization of Advanced Control Strategies for Parallel Kinematics - Flottmeier, Sarah; Olma, Simon; Trächtler, Ansgar (Proceedings of the 19th IFAC World Congress)

Control of Pareto Points for Self-Optimizing Systems with Limited Objective Values - Kessler, Jan Henning; Trächtler, Ansgar (The 19th IFAC World Congress)

Joint Selection Criterion for Optimal Trajectory Planning for Robotic Manipulators Using Dynamic Programming - Shareef, Zeeshan; Trächtler, Ansgar (19th IFAC World Congress)

Analyses of the stress-strain behaviour of SMAs under cyclical loading conditions – implementation of a novel phenomenological constitutive model - Pai, Arathi; Krooß, Philipp; Niendorf, Thomas; Koke, Isabel; Trächtler, Ansgar; Schaper, Mirko (Posterbeitrag ICOMAT - International Conference on Martensitic Transformations, Juli 2014, Bilbao, Spanien)

Concept for a self-correcting sheet metal bending operation

Design and Control of a Vertical Ball Juggling Delta Robot without Visual Guidance - Shareef, Zeeshan; Just, Viktor; Teichrieb, Heinrich; Trächtler, Ansgar (13th International Conference on Intelligent Autonomous Systems)

Configuration of Mechatronic Systems Using Feature Models - Abrishamchian, Farisoroosh; Trächtler, Ansgar (2nd International Conference on System-Integrated Intelligence)

Selbstkorrigierende Biegeprozesse in der Umformtechnik

Continuous Objective-based Control for Self-Optimizing Systems with Changing Operation Modes - Kessler, Jan Henning; Krüger, Martin; Trächtler, Ansgar (13th European Control Conference (ECC))

Semantische Technologien im Entwurf mechatronischer Systeme: Effektiver Austausch von Lösungswissen in Branchenwertschöpfungsketten - Gausemeier, Jürgen; Trächtler, Ansgar; Schäfer, Wilhelm; Anacker, Harald; Bauer, Frank; Borcherding, Holger; Dziwok, Stefan; Frank, Ursula; Herden, Rudolf; Hoppe, Gerd; Just, Viktor; Kiele-Dunsche, Markus; et al.

Model-based design of self-correcting forming processes - Krüger, Martin; Borsig, Michael; Schaermann, Waldemar (KoMSO Challenge Workshop Math for the Digital Factory)

RAILCAB – THE INNOVATIVE PLATFORM FOR DESIGN AND TEST OF NEW RAILWAY TECHNOLOGIES

Test Rig for the Hardware-in-the-Loop Simulation of Mechatronic Axles - Flottmeier, Sarah; Jäker, Karl-Peter; Trächtler, Ansgar (Proceedings of the 9th International Fluid Power Conference)

A Modelica Contact Library for Idealized Simulation of Independently Defined Contact Surfaces - Oestersötebier, Felix; Wang, Peng; Trächtler, Ansgar (10th International Modelica Conference)

3.1 Sensoren für die digitale Produktion - Klocke, Fritz; Trächtler, Ansgar; Henke, Christian (Integrative Produktion - Industrie 4.0)

Development of the RailCab Vehicle - Flaßkamp, Kathrin; Grösbrink, Stefan; Hartmann, Philip; Heinzemann, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Ober-Blöbaum, Sina; Priesterjahn, Claudia; Rasche, Christoph; Schäfer, Wilhelm; Steenken, Dominik; et al. (Dependability of Self-Optimizing Mechatronic Systems)

Verification for Interacting Mechatronic Systems with Motion Profiles - Flaßkamp, Kathrin; Heinzemann, Christian; Krüger, Martin; Ober-Blöbaum, Sina; Schäfer, Wilhelm; Steenken, Dominik; Trächtler, Ansgar; Wehrheim, Heike (Dependability of Self-optimizing Mechatronic Systems)

Control strategies on stable manifolds for energyefficient swing-ups of double pendula - Flaßkamp, Kathrin; Timmermann, Julia; Ober-Blöbaum, Sina; Trächtler, Ansgar (International Journal of Control)

Hierarchical Modelling of Mechatronic Systems - Krüger, Martin; Trächtler, Ansgar (Design Methodology for Intelligent Technical Systems)

Fahrzeugdynamikmodelle für Echtzeitsimulationen im komfortrelevanten Frequenzbereich - Amelunxen, Hendrik

Selbstoptimierende Spurführung für ein neuartiges Schienenfahrzeug - Geisler, Jens

Parametrische Modellordnungsreduktion für hierarchische selbstoptimierende Systeme - Krüger, Martin

Architecture of Self-optimizing Systems - Krüger, Martin; Trächtler, Ansgar (Design Methodology for Intelligent Technical Systems)

Autonomously driven railway cabin convoys — Communication, control design and experimentation - Henke, Christian; Trächtler, Ansgar (2013 International Conference on Connected Vehicles and Expo (ICCVE))

Mechatronischer Entwurf und Erprobung einer regelbaren Federung für ein leichtes geländegängiges Kettenfahrzeug - Illg, Igor

Entwurf mechatronischer Fahrzeugfederungen am Beispiel eines geländegängigen Nutzfahrzeugs - Wielenberg, Andreas

Optimale Steuerung und Mehrzieloptimierung von dynamischen Systemen untersucht am Beispiel des Mehrfachpendels - Timmermann, Julia
In dieser Arbeit wird gezeigt, wie optimale Trajektorien für ein unteraktuiertes mechanisches System - das Doppel- bzw. Dreifachpendel auf einem Wagen - mittels optimaler Steuerung bestimmt werden können. Dabei werden neuartige mathematische Methoden verwendet und deren Vorteile in der Anwendung aufgezeigt. Es werden sowohl die theoretischen Ergebnisse analysiert als auch die praktische Umsetzung in Simulationen und am Prüfstand untersucht. Das Manöver, welches hier hauptsächlich betrachtet wird, ist der Aufschwung des Pendels aus der stabilen unteren Ruhelage in die instabile obere Ruhelage. Dabei werden mit Hilfe von Methoden der Mehrzieloptimierung viele Varianten von Lösungen berechnet, die die zwei gegenläufigen Zielgrößen Dauer des Manövers und Steueraufwand unterschiedlich stark berücksichtigen. So ist es möglich eine komplexe Bibliothek von optimalen Lösungen zu erhalten und diese weitergehend bezüglich des Gesamtsystemverhaltens zu analysieren. Ein weiterer Ansatz ist die Entwicklung von Strategien für eine optimale Steuerung auf Mannigfaltigkeiten, die besondere dynamische Strukturen des Pendelsystems für einen optimalen Aufschwung nutzen. Auf der stabilen Mannigfaltigkeit kann sich das dynamische System kostenlos in die Ruhelage bewegen. Dies ist somit ein besonderer physikalisch motivierter Ansatz, um optimale Manöver zu finden.

Coordination of Multiple Autonomous Intersections by Using Local neighborhood information - Wuthishuwong, Chairit; Trächtler, Ansgar (Proc. IEEE International Conference on Connected Vehicles and Expo)

Automated Design of an Unscented Kalman Filter for State- and Parameter Estimation on unknown Models - Schweers, Christoph; Trächtler, Ansgar; Kruse, Daniel (Control, Automation, Robotics & Embedded Systems)

Vehicle to Infrastructure based Safe Trajectory Planning for Autonomous Intersection Management - Wuthishuwong, Chairit; Trächtler, Ansgar (Proc. IEEE International Conference on ITS Telecommunication (ITST))

Dynamical Model of Ball Juggling Delta Robots using Reflection Laws - Shareef, Zeeshan; Just, Viktor; Teichrieb, Heinrich; Lankeit, Christopher; Trächtler, Ansgar (16th International Conference on Advanced Robotics (ICAR))